Media coverage of the sports journalist's matches at the Algerian competition - حديبي , سعيد (sports creativity, 2025)
This study aims to know the extent of the important role of the media coverage of the matches of the Algerian national team in the competitions of the sports journalists by knowing their opinions about the working conditions inside the stadiums. 40 journalists and sports correspondents from various national newspapers, and this is to conduct the basic study. We used a questionnaire on media coverage for the participation of the Algerian national team, consisting of three axes, the axis of general statements and the two axes to address the hypotheses put forward, and at the conclusion of this study we concluded that the sports journalist does not find all the material means inside the stadiums. Sports during media coverage, and stadium management does not guarantee effective communication with journalists to facilitate their tasks during media coverage of sports matches